Chronic Pain Self-Management Program for Low-Income Patients: Themes from a Qualitative Inquiry. Issue 2 (11th October 2018) - Turner, Barbara J; Rodriguez, Natalia; Bobadilla, Raudel; Hernandez, Arthur E; Yin, Zenong
Abstract: Objective: To examine factors influencing initial engagement, ongoing participation, learned behaviors, and subjective functional outcomes after a trial of the Living Better Beyond Pain (LBBP) chronic pain self-management program. Design: Qualitative study using the Grounded Theory approach. Setting: Two 60-minute focus groups and phone interviews in May 2017. Subjects: Focus groups with 18 participants who completed LBBP and six-month measures; telephone interviews with 17 participants who stopped attending. Methods: Study coordinators randomly selected program completers for focus groups and conducted phone interviews with noncompleters. Inductive thematic analysis was used to identify patterns in semantic content with a recursive process applied to focus group transcripts and interview transcriptions to codify into themes. Themes were categorized according to the Theory of Planned Behavior. Results: Focus group and telephone interview participants were primarily Hispanic and unemployed. Attitudes fostering participation in LBBP included dissatisfaction with the status quo, need to reduce pain medication, and lack of training and knowledge about chronic pain. Positive social norms from meeting others with chronic pain and support from the LBBP team encouraged attendance and adoption of behaviors. Transportation, pain, and competing activities were barriers, whereas adapting activities for the disabled was a facilitator. Maintaining behaviors and activities at home was challenging but ultimately rewarding due to improvement in daily function with less pain medication. Conclusions: This qualitative study complements quantitative results showing clinically significant improvements in function after the LBBP program by adding practical insights into ways to increase participation and outcomes. Participants strongly endorsed the need for chronic pain self-management training.